Pengetahuan, sikap dan amalan penggunaan racun makhluk perosak serta faktor yang mempengaruhinya di kalangan petani Tanjung Karang Selangor - Mahasiswa/wi Perubatan Fasa 2 Kumpulan 6 Sesi 1997/98 (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1998)
A cross sectional study on the knowledge, attitude and practice of pesticide use among users aged between 18 - 60 years old was carried out in Kampung Sri Gambut, Sungai Burung, Tanjung Karang Selangor between 7 - 9 October 1997. There were 160 respondents who are a pesticide users. Data was collected through interviews by using guided questionaire. Observational study was also done at six licensed pesticide dealers at Sekinchan and another two at Tanjung Karang itself. The results obtained showed that 43.8% users have low knowledge whereas 51.3% have wrong attitude towards pesticide use. It was also found that 48.8% users had experienced clinical signs and symptoms of pesticide poisoning like headache and skin irritation. Only 46.9% users obtained the information about pesticides through mass media while the remainder are from other sources. A descriptive study done showed that 60.6% users still practice traditional beliefs related to pesticide use. A three day implementation programme was done to increase the knowledge among pesticide users. It was found that there was a significant increase in their knowledge after the programme.